Optimized LC-MS method for simultaneous polyamine profiling and ADC/ODC activity quantification and evidence that ADCs are indispensable for flower development in tomato - Ritchie, Erin Samantha; von Roepenack-Lahaye, Edda; Perrett, Dennis; Wu, Dousheng; Lahaye, Thomas (Frontiers in Plant Science, 2025)
IntroductionPolyamines (PAs) are essential for plant development and stress responses, requiring tight homeostatic regulation. As many PA enzymes are regulated post-transcriptionally, transcript-based methods cannot accurately predict protein abundance. This limitation highlights the need for alternative approaches to study PA homeostasis.MethodsWe optimized a liquid chromatography–mass spectrometry (LC-MS)–based method to simultaneously quantify the activities of two key PA-synthesizing enzymes—arginine decarboxylase (ADC) and ornithine decarboxylase (ODC)—from plant tissues using stable isotope substrates. Substrate concentrations were optimized to increase assay sensitivity, and the method was adapted for Nicotiana benthamiana as a heterologous expression system.ResultsIn tomato leaf tissue, assay sensitivity improved more than tenfold. In N. benthamiana, expression of epitope-tagged ADCs revealed a direct correlation between protein abundance and enzymatic activity, indicating that ADC activity can infer native protein abundance. Proof-of-principle experiments confirmed substrate specificity of tomato ADC and ODC enzymes and identified essential catalytic residues of tomato ADCs. The protocol was further expanded to quantify 11 PA-network metabolites from the same LC-MS sample—six more than previously reported—providing a comprehensive overview of PA metabolism when visualized as a pathway heatmap. LC-MS analysis of tomato CRISPR–Cas9 mutants deficient in ADC or ODC, revealed that the adc1/adc2 double mutant had no detectable agmatine and reduced putrescine, whilst spermidine and spermine remained unaffected. Phenotypic analysis showed severe developmental defects in this mutant, including complete flower loss, underscoring the indispensable role of ADCs in flower development.DiscussionTogether, the optimized LC-MS method, the ability to functionally analyze recombinant ADC/ODC proteins in planta, and the use of tomato CRISPR mutants provide a versatile toolkit to dissect PA homeostasis and PA-dependent developmental processes in plants.